A Spectrum Sharing Mechanism Between Narrowband M2M System and LTE System - Guoping Chen; Qingbo Du (Dianxin kexue)
Long term evolution（LTE）networks is an advanced mobile broadband network defined in 3GPP（3rd Generation Partnership Project）,to satisfy the human to human communication requirement.With the quick developing of machine to machine communication requirement,how to deploy the M2M networks with a high speed,low cost and efficient manner is the definite requirement in the industry.A low cost M2M network which deploy co-sited with MBB networks and shared spectrum with MBB network was proposed.System simulations show the spectrum sharing mechanism can solve the inter-RAT interference influence and ensure the acceptable performance loss.And the mechanism is low cost and technical reasonable.